2012
DOI: 10.1007/s11103-012-9892-3
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, functional characterization and heterologous expression of TaLsi1, a wheat silicon transporter gene

Abstract: Silicon (Si) is known to be beneficial to plants, namely in alleviating biotic and abiotic stresses. The magnitude of such positive effects is associated with a plant's natural ability to absorb Si. Many grasses can accumulate as much as 10% on a dry weight basis while most dicots, including Arabidopsis, will accumulate less than 0.1%. In this report, we describe the cloning and functional characterization of TaLsi1, a wheat Si transporter gene. In addition, we developed a heterologous system for the study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
138
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(145 citation statements)
references
References 38 publications
4
138
0
3
Order By: Relevance
“…Similar findings were observed in wild and cultivated rice (Mitani-Ueno et al 2013). In addition to rice, similar Si transporters were found in other grasses such as maize, barley and wheat (Mitani et al 2009a, b;Chiba et al 2009;Montpetit et al 2012;Yamaji et al 2012).…”
Section: Introductionsupporting
confidence: 73%
“…Similar findings were observed in wild and cultivated rice (Mitani-Ueno et al 2013). In addition to rice, similar Si transporters were found in other grasses such as maize, barley and wheat (Mitani et al 2009a, b;Chiba et al 2009;Montpetit et al 2012;Yamaji et al 2012).…”
Section: Introductionsupporting
confidence: 73%
“…More recently, TaLsi1 a wheat Si transporter gene has been cloned (Montpetit et al 2012 ). Barley HvLsi1, corn ZmLsi1 and wheat TaLsi1 showed a high level of homology with rice OsLsi1 Montpetit et al 2012 ).…”
Section: Other Monocotsmentioning
confidence: 99%
“…More recently, TaLsi1 a wheat Si transporter gene has been cloned (Montpetit et al 2012 ). Barley HvLsi1, corn ZmLsi1 and wheat TaLsi1 showed a high level of homology with rice OsLsi1 Montpetit et al 2012 ). Both HvLsi1 and ZmLsi1 show Si infl ux transport activity as OsLsi1, however, with different localization and expression patterns than observed in rice .…”
Section: Other Monocotsmentioning
confidence: 99%
“…Silicon accumulation in natural systems is rarely linked to adverse effects in plants, even in those that have a high Si uptake capacity (Cooke and Leishman, 2011). Montpetit et al (2012) also reported that the Si absorption caused leaf necrosis in Arabidopsis and this symptom was proportional to the external Si concentration. Further, they assumed that this symptom was caused by improper regulation of Si uptake or transport in Arabidopsis transformants.…”
Section: Introductionmentioning
confidence: 99%